FRI0742-HPR Does the use of technological devices improve the reliability of measuring the active cervical range of motion in patients with neck pain? a systematic review with meta-regression. (15th June 2017) - Rondoni, A; Rossettini, G; Strobe, M; Gallo, F; Ristori, D; Testa, M
Abstract : Background: Economic impact of neck pain shows an increasing trend. In order to limit the costs of spine disorders management, it is important to assess clinical efficacy and the cost-worthiness of new technological devices, recently introduced in physical therapist's clinical practice Objectives: This systematic review compares, in patients with non-specific neck pain, the reliability of measures of Active Cervical Range of Motion (ACROM) detected with technological devices with those assessed with low cost, common-use devices. As secondary outcomes, it was investigated if ACROM reliability depends on the plane on which the measured movement is performed Methods: The literature search was carried out in Medline, Scopus, Embase, The Cochrane Library, CINHAL, PEDro and grey literature until August 2016. Inclusion criteria were: reliability design, population of adults with nonspecific neck pain, examiners of any level of experience, measures repeated at least twice and statistics indexes on reliability. Exclusion criteria were: other study designs, asymptomatic population or mixed population, single or none ACROM measure, inadequate statistics. The risk of bias was assessed by QAREL. It was considered inexpensive a device that costs at maximum 500 euros. A Univariate, and a Multivariate Analysis, were performed by using the Linear Mixed-Effect Model Results: Searching the databases yielded 35, 151 records. Nine studies met all eligibility criteria. The QAREL mean score of the selected studies was 3.7 out of 11. No significant effect of the type of device (inexpensive versus expensive) on ICC was observed for intra-rater (ICC=0.93vs0.91 p-value>0.99) and inter-rater reliability (ICC=0.80vs0.87 p-value>0.99) [Table 1 ]. The plane of movement did not affect inter-rater reliability (p-value=0.11) while significantly influenced the intra-rater reliability (p-value=0.0001) assessed with low-cost devices. Intra-rater reliability significantly decreases (p-value=0.0129) in frontal plane movements (side bending) compared with movement on the sagittal plane (flexion-extension). Conclusions: The use of expensive devices to measure ACROM in adults with nonspecific neck pain does not seem to improve the reliability of the assessment. The assessment of side bending showed the lowest level of inter-raters reliability. Since the quality of the analysed studies is low, the conclusion of the present study should be taken cautiously Disclosure of Interest: None declared